Behavioral Control, Entrepreneurial Activity, and Entrepreneurship Education: The Mediating Role of Entrepreneurial Attitude in Shaping Entrepreneurial Interest - Tika Handayani; Rosita Rosita (Indonesian Journal of Business and Entrepreneurship Research, 2025)
Unemployment is a major issue in Indonesia. This is due to Indonesia being a country with a relatively high population growth rate, which impacts competition for job opportunities. One effective way to address unemployment is by creating or increasing the number of entrepreneurs. This study aims to determine the direct and indirect effects of entrepreneurship education, behavioral control, entrepreneurial activity, and entrepreneurial attitude on entrepreneurial interest. The sampling technique used was Proportional Random Sampling, with a total of 106 students at Politeknik Negeri Sriwijaya. The research results indicate that both directly and indirectly, entrepreneurship education, behavioral control, entrepreneurial activity, and entrepreneurial attitude have a significant impact on entrepreneurial interest. Based on the findings of this study, it can serve as a source of information or reference for educators or lecturers to guide and mentor students regarding the development of entrepreneurial skills. Students are expected to deepen their skills related to business management so that they focus not only on the products produced but also on marketing activities and decision-making regarding business evaluation, with the aim of developing their businesses. Furthermore, future researchers are encouraged to deepen and expand this research in terms of variables and the development of research methods.